1997
DOI: 10.1128/jcm.35.3.563-565.1997
|View full text |Cite
|
Sign up to set email alerts
|

Doing it right the first time: quality improvement and the contaminant blood culture

Abstract: The aim of the project was to determine whether the rate of contaminant blood cultures could be reduced by using a team of dedicated phlebotomists. Comparisons were made between adult patients requiring blood cultures for suspected bacteremia on medical and surgical units before and after the introduction and withdrawal of a dedicated blood culture team. The results showed that a significant reduction in the contaminant blood culture rate was achieved by the blood culture team (P < 0.001; chi(2) test). Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(45 citation statements)
references
References 9 publications
3
38
1
2
Order By: Relevance
“…Only limited data are available concerning the association between the expertise of staff members and the risk of BCC. Previous studies have shown that trained phlebotomists are associated with lower BCC rates than resident physicians [4,15,16]. In the present study, the gender and status of personnel were not associated independently with BCC, and younger physicians performed no worse than those with more experience.…”
Section: Introductioncontrasting
confidence: 60%
“…Only limited data are available concerning the association between the expertise of staff members and the risk of BCC. Previous studies have shown that trained phlebotomists are associated with lower BCC rates than resident physicians [4,15,16]. In the present study, the gender and status of personnel were not associated independently with BCC, and younger physicians performed no worse than those with more experience.…”
Section: Introductioncontrasting
confidence: 60%
“…Several studies have suggested methods to reduce blood culture contamination, 7 including standardization of collec-impact of contaminated blood cultures 3 tion technique and utilization of blood culture sample collection teams. 6,[8][9][10] Our study suggests that substantial unnecessary interventions and possible adverse outcomes can be attributed to blood culture contamination. Implementation of known mechanisms to reduce blood culture contamination more broadly and investigation of further techniques for contamination reduction can, hopefully, prevent such events.…”
Section: Resultsmentioning
confidence: 99%
“…The contamination rates of blood cultures collected by phlebotomists were significantly lower than the rates for blood cultures obtained by nonphlebotomists in the emergency department (3.1% vs. 7.4%) [4]. Introduction of a dedicated blood culture team significantly reduced the blood culture contamination rate in the other studies [5,18,19].…”
Section: Frequency Of Staphylococcus Aureus Klebsiella Pneumoniae Ormentioning
confidence: 93%